Perlindungan Konsumen dalam Layanan Umum: Analisis Regulasi dan Implementasi Kebijakan terhadap Hak-hak Konsumen - Maratus, Ana; Syafi'iyah, Latifatus (Forschungsforum Law Journal, 2025)
Consumer protection in public services is a crucial element in ensuring justice and legal certainty for the public. This study aims to analyze consumer protection regulations and the implementation of policies supporting the fulfillment of consumer rights in public services. The research problem addressed is the extent to which existing regulations provide effective protection and how policies are implemented in practice. The research method used is normative juridical with a statutory and case study approach. The findings show that although the regulatory framework is available, its implementation faces various challenges, such as weak supervision, lack of public outreach, and suboptimal consumer dispute resolution. This study recommends strengthening regulations, enhancing the capacity of supervisory institutions, and fostering synergy among agencies to achieve effective consumer protection in the public service sector.